PENGARUH PENAMBAHAN PERAK PADA MOLEKUL DYE TERHADAP EFISIENSI DYE SENSITIZED SOLAR CELL - Rati Okta Della; Iwantono Iwantono (Komunikasi Fisika Indonesia, 2021)
Dye sensitized solar cell (DSSC) is made with a layer arrangement of fluorine tin oxide (FTO), zinc oxide (ZnO), dye, electrolyte, and plastisol. ZnO nanorods which play a role as photoanode in DSSC have been successfully grown on FTO substrate using seed mediated hydrothermal method at temperature of 90 ºC for 8 hours. Modification was made to increases the efficiency of DSSC by adding silver (Ag) with concentration of 5 mM into dye molecules. ZnO characterization was performed using ultra violet-vissible (UV-Vis) spectroscopy and field emission scanning electron microscopy (FESEM). The strongest UV-Vis absorbance spectrum with the optimum absorbance for the ZnO sampel was occurred at the wavelength range of 300 – 360 nm. Meanwhile, for the ZnO sample with addition of 5 mM Ag into dye molecule was occurred at the wavelength range of 440 – 530 nm. FESEM image of the sample shows the as-synthesized ZnO nanorods have hexagonal cross section. I-V characteristics in the light mode was carried out to determine the efficiency of DSSC using  a halogen lamp with an intensity of 100 mW/cm2. The efficiency of DSSC using ZnO with addition of 5 mM Ag into dye molecule is 0.462%, increases compared to the efficiency of DSSC using ZnO without addition of Ag into dye molecule which only produce 0.45% efficiency. These results indicate that the addition of Ag can increase the efficiency of DSSC.